2018
DOI: 10.1177/0269215518787338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of upper limb resistance exercise on aerobic capacity, muscle strength, and quality of life in COPD patients: a randomized controlled trial

Abstract: Upper limb resistance exercise improved the exercise capacity, respiratory muscle strength, and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 41 publications
1
30
0
7
Order By: Relevance
“…The total number of subjects included in this study was 514. Twelve studies reported no between-group differences in subject characteristics [22-33]. One study reported significantly lower mean body weight in the UL training group than that in the control group [34].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The total number of subjects included in this study was 514. Twelve studies reported no between-group differences in subject characteristics [22-33]. One study reported significantly lower mean body weight in the UL training group than that in the control group [34].…”
Section: Resultsmentioning
confidence: 99%
“…According to the GOLD classification of the severity of COPD, included studies were divided as follows: (1) nine studies had individuals with severe COPD [22-29,34], (2) four studies had individuals with moderate COPD [30-33], and (3) two studies [35,36] did not describe the percentage of the predicted FEV 1 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gejala yang dirasakan pasien pada umumnya adalah batuk berdahak yang semakin parah pada saat pagi hari, sesak nafas, dan penurunan kemampuan atau ketahanan dalam melakukan aktivitas (Malini, Fatmadona, Rahman, & Afriyanti, 2018 Pursed lip breathing dan pernapasan diafragma yang diberikan pada pasien PPOK dapat disertai dengan peregangan pada otot-otot tubuh bagian atas (upper limb stretching). Peregangan pada otot tubuh akan meningkatkan massa otot, kekuatan, dan ketahanan dalam melakukan aktivitas atau proses latihan fisik (Silva, Neto, Saquetto, Conceicao, & Machado, 2018). Peregangan otot tubuh bagian atas juga mampu mengoptimalkan fungsi neuromekanik dari otot pernapasan yang menurun pada pasien PPOK (Kaymaz et al, 2018).…”
Section: Pendahuluanunclassified